2020
DOI: 10.3390/ijerph17134659
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Disinfection Byproducts in Public Swimming Pools in Medellín, Colombia

Abstract: The quality of water in swimming pools is essential to avoid risks to the health of users. Medellín has more than 1000 public swimming pools, which are supervised by the Medellín Health Authority to monitor and ensure compliance with relevant regulations. The Health Authority has financed several studies related to the quality of drinking and recreational water in Medellín in order to protect consumers and users. One such study involves the evaluation of the presence of disinfection byproducts (DBP). The best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…In swimming pool waters, nitrogenous DBPs have been shown to be generally more genotoxic (to Chinese hamster ovary cells) compared to most other DBPs [ 13 , 25 ], and greater toxicological effects were found to be associated with HANs than with THMs and HAAs [ 43 , 48 , 53 , 54 ]. Toxicological studies showed that HANs are more genotoxic and cytotoxic than THMs or HAAs [ 2 , 13 , 26 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In swimming pool waters, nitrogenous DBPs have been shown to be generally more genotoxic (to Chinese hamster ovary cells) compared to most other DBPs [ 13 , 25 ], and greater toxicological effects were found to be associated with HANs than with THMs and HAAs [ 43 , 48 , 53 , 54 ]. Toxicological studies showed that HANs are more genotoxic and cytotoxic than THMs or HAAs [ 2 , 13 , 26 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some unregulated DBPs are stressors with strong cytotoxicity and genotoxicity [4]. The skin as the body's largest organ is exposed to DBPs during bathing and swimming [5]. However, few investigations have focused on nitrogenous DBPs in skin, the important target organ.…”
Section: Introductionmentioning
confidence: 99%